2020
DOI: 10.3390/biom10010122
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Regulation of Th17 Cell Responses and Autoimmune Neuro-Inflammation by Ginsenoside Rg3

Abstract: Among diverse helper T-cell subsets, Th17 cells appear to be pathogenic in diverse autoimmune diseases, and thus, targeting Th17 cells could be beneficial for the treatment of the diseases in humans. Ginsenoside Rg3 is one of the most potent components in Korean Red Ginseng (KRG; Panax ginseng Meyer) in ameliorating inflammatory responses. However, the role of Rg3 in Th17 cells and Th17-mediated autoimmunity is unclear. We found that Rg3 significantly inhibited the differentiation of Th17 cells from naïve prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“… 53 Seven studies were retrieved specifically on the use of Ginseng for EAE. 54 , 55 , 56 , 57 , 58 , 59 , 60 Ginseng can be classified according to their countries of origin: Panax ginseng or Korean Ginseng (人参 rén shēn ), Panax japonicus or Japanese ginseng , Panax notoginseng or Chinese ginseng (三七 sān qī ), Panax quinquefolius or American Ginseng (西洋参 xī yáng shēn ), and Panax vietnamensis or Vietamese ginseng . 61 In general, the plants of the genus Panax have important pharmacological activities attributed to its main active principle, a saponin, known as ginsenoside .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 53 Seven studies were retrieved specifically on the use of Ginseng for EAE. 54 , 55 , 56 , 57 , 58 , 59 , 60 Ginseng can be classified according to their countries of origin: Panax ginseng or Korean Ginseng (人参 rén shēn ), Panax japonicus or Japanese ginseng , Panax notoginseng or Chinese ginseng (三七 sān qī ), Panax quinquefolius or American Ginseng (西洋参 xī yáng shēn ), and Panax vietnamensis or Vietamese ginseng . 61 In general, the plants of the genus Panax have important pharmacological activities attributed to its main active principle, a saponin, known as ginsenoside .…”
Section: Discussionmentioning
confidence: 99%
“… 58 The ginsenoside Rg3 is one of the most potent anti-inflammatory components of Korean red ginseng (红参 hóng shēn ). 60 Although P. ginseng (人参 rén shēn ) is used in the formulas BZYQT and HQRST , we included in this review other species of ginseng used in controlled clinical trials that treated EAE/MS due to their similar pharmacological properties. We also found seven articles on Glycyrrhizae radix (甘草 gān cǎo ), and its isolates which affected EAE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In autoimmune diseases, IL-17A-producing CD4 + T cells (Th17) were recognized as critically pathogenic immune cells that mediate tissue inflammation. Park et al demonstrated that ginsenoside Rg3 inhibited Th17 differentiation as well as Th17-mediated neuro-inflammation in a dendritic cell-T co-culture system [9]. The authors suggested that Rg3 could be a potential agent for treating certain autoimmune disorders driven by Th17 cells.…”
Section: Bioactivitiesmentioning
confidence: 99%